Analysis Of Factors That Influence The Performance Of Employees In Boarding And Unloading Of Ship Goods In The Port - Iswandi Iswandi; Muji Gunarto; Andriyansah Andriyansah (Green Publisher Indonesia, 2024)
The activity of loading and unloading ship goods at the port is one of the vital activities in the goods distribution chain. The performance of employees involved in this process has a direct impact on port efficiency and productivity as well as safety and security in its operations. However, in practice, a variety of factors might impact employee effectiveness in these activities. The aim of this research is to analyze the factors that influence the performance of employees involved in loading and unloading ship cargo activities at the port. This study0 uses quantitative research methods by collecting data through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that the factors that influence the performance of employees loading and unloading ship goods at the port include supervision, human resource competency and job security. Therefore, to improve employee performance, efforts need to be made such as strengthening the monitoring and control system for employee performance, improving employee training and competency development, and creating safe and comfortable working conditions for employees.